Sequestration of erythrocytes infected with Plasmodium berghei ANKA in BALB/c mice treated with goat bile - Kartika Arum Wardani; Kholida Nur Aini; Heny Arwati; Willy Sandhika (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
Abstract Sequestration of Plasmodium berghei ANKA-infected erythrocytes occurs in BALB/c mice as characteristic of  Plasmodium falciparum infection in humans. Animals’ bile has been widely used for centuries in Traditional Chinese Medicine. Goat bile has been used in healing infectious and non-infectious diseases; however, no report on the use of goat bile against malaria infection and sequestration. The purpose of this study was to analyze the correlation between parasitemia and sequestration in the liver of P.berghei ANKA-infected BALB/c mice treated with goat bile. This research was an in vivo experimental study using the post-test control group design. The male BALB/c mice aged ± 6 weeks, body weight 20-25 g were used. The mice were divided into five groups where Group 1-3 were mice treated with goat bile 25%, 50%, and 100%, respectively. Group 4-5 were negative (sterile water) and positive controls (DHP). Parasitemia was observed daily from each mouse and the number of sequestered infected erythrocytes on the endothelium of sinusoids. The data were analyzed using t independent test. Antimalarial activity of goat bile was shown by the lower parasitemia in goat bile-treated mice compared with the negative control. The average number of sequestration was goat bile concentration-dependent manner. The higher the concentration, the lower the number of sequestration. Sequestration was correlated with parasitemia (p=0,0001). Sequestration of P.berghei ANKA-infected erythrocytes correlated with parasitemia, and was goat bile concentration-dependent manner. Keywords: Malaria, parasitemia, sequestration, goat bileCorrespondence: arwatiheny@gmail.com